(untitled) (Bangladesh Heart Journal, 2019)
Introduction: Diabetes mellitus has been associated with an increased risk of adverse outcome after coronary artery bypass graft surgery. HbA1c is a reliable measure of long-term glucose control. It is unknown whether adequacy of diabetic control, measured by hemoglobin A1c, is a predictor of adverse outcomes after coronary artery bypass grafting. The predictive role of HbA1c on short term outcomes after coronary artery bypass graft surgery has not been evaluated. Diabetes mellitus has become a major health issue and contributes to morbidity and mortality from coronary artery disease. The purpose of this study is to determine the predictive role of preoperative elevated HbA1c on post-operative outcome in CABG patients. Objectives: This study evaluates the early postoperative outcomes of CABG in terms of mortality and major postoperative morbidities like deep sternal wound infection, sepsis, stroke, renal failure, bleeding, arrhythmia, and mediastinitis in patients with preoperative elevated level of HbA1c. Methods: This prospective study was done in National Institute of Cardiovascular Diseases (NICVD). Patients of coronary artery disease (CAD) with DM referred for CABG were enrolled for the study. Total 60 patients were allocated into two groups. Among them 30 patients with preoperative HbA1c of <7% and another 30 patients with preoperative HbA1c of > 7 % underwent CABG surgery from January, 2009 to December, 2010. The early postoperative outcomes were compared between two groups. Both groups were matched with no significant difference that could influence the postoperative outcome. Results: In-hospital mortality was high in patients with preoperative elevated level of HbA1c. An elevated hemoglobin A1c level predicted in-hospital mortality after CABG surgery. Our study revealed that HbA1c greater than 7 % was associated with increase in mortality. For each unit increase hemoglobin A1c , there was a significantly increase risk of myocardial infarction and deep sternal wound infection. By using receiver operating characteristic value thresholds, renal failure, cerebrovascular accident and deep sternal wound infection occurred more commonly in patients with elevated hemoglobin A1c. Morbidity, infections and the composite outcomes occurred more commonly in patients with elevated HbA1c. Conclusion: Elevated HbA1c is strongly associated with adverse events after coronary artery bypass graft surgery. Preoperative HbA1c measurement may allow for more accurate risk stratification in patients undergoing coronary artery bypass graft surgery. Bangladesh Heart Journal 2019; 34(2) : 92-99